The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2006
DOI: 10.4049/jimmunol.177.5.3100
|View full text |Cite
|
Sign up to set email alerts
|

Expression and Release of HLA-E by Melanoma Cells and Melanocytes: Potential Impact on the Response of Cytotoxic Effector Cells

Abstract: HLA-E are nonclassical MHC molecules with poorly characterized tissue distribution and functions. Because of their capacity to bind the inhibitory receptor, CD94/NKG2A, expressed by NK cells and CTL, HLA-E molecules might play an important role in immunomodulation. In particular, expression of HLA-E might favor tumor cell escape from CTL and NK immunosurveillance. To address the potential role of HLA-E in melanoma immunobiology, we assessed the expression of these molecules ex vivo in human melanoma biopsies a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
123
4
2

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 139 publications
(143 citation statements)
references
References 58 publications
(60 reference statements)
14
123
4
2
Order By: Relevance
“…IFN-g has earlier been reported to protect ovarian carcinoma and melanoma cells from lysis through a CD94/NKG2A-dependent pathway. 17,22 Similar effects are reported during virus infections. Tomasec et al 23 showed that co-infection of fibroblasts with high amounts of recombinant adenovirus encoding HLA-E and UL40 CVM protein results in increase of HLA-E expression and protection against NK lysis through CD94/NKG2A.…”
Section: Discussionsupporting
confidence: 68%
“…IFN-g has earlier been reported to protect ovarian carcinoma and melanoma cells from lysis through a CD94/NKG2A-dependent pathway. 17,22 Similar effects are reported during virus infections. Tomasec et al 23 showed that co-infection of fibroblasts with high amounts of recombinant adenovirus encoding HLA-E and UL40 CVM protein results in increase of HLA-E expression and protection against NK lysis through CD94/NKG2A.…”
Section: Discussionsupporting
confidence: 68%
“…Under physiological conditions, HLA-E is mainly involved in maternal immune tolerance. HLA-E is abberantly expressed in several tumors like lymphoma (Marin et al, 2003), melanoma (Derre et al, 2006), colon carcinoma (Bianchini et al, 2006), ovarian cancer (Malmberg et al, 2002) and may contribute to immunosuppression in glioblastoma (Mittelbronn et al, 2007;Wischhusen et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…14,15 These observations were extended to the sera of nonalloimmunized males to document that the observed HLA-Ia reactivity in human sera could be due to anti-HLA-E Abs. 13 To ascertain whether immunizing humans with HLA-E would augment anti-HLA-E Abs with HLA-Ia reactivity, we examined sera of melanoma patients immunized with autologous melanoma cells grown in interferon-g (IFN-g), a cytokine known to induce overexpression of HLA-E. [16][17][18] The immunized patients not only showed the augmentation of anti-HLA-E Abs, confirming the immunogenicity of HLA-E in humans, but also showed increased reactivity with HLA-Ia (single antigen) coated onto microbeads. 18 Indeed, the pattern of HLA-Ia reactivity in immunized patients corresponded with the pattern of HLA-Ia reactivities exhibited by some of the anti-HLA-E mAbs.…”
Section: Introductionmentioning
confidence: 99%